Military Careers, Family and Private Dilemmas - Romão, Ana (2015)
Work and family are the two most important areas of life for most people. Although the two are traditional areas of sociological study, and have occupied diferent ields of research. Today, the characteristics of these social institutions in contemporary society reinforce the need to discuss the relationship between work and family in the context of the social sciences, and very particularly in sociology. Interest of study that is even more evident in the ield of the military profession, given the speciicities associated with her, and also by the changes in society and the military. A signiicant number of studies have enlighten the impact of military life on families, considering that the circumstances of risk, frequent mobility, long absences, uncertainty etc. products remarkable efects not only in military service personnel, but also in those who are close to them. Family and the military organization have in common the fact of being extraordinarily demanding in ties, energy and total dedication. Using the terms of Segal (1988), the “greediness” of both institutions may lead to conlicts between the family and the military realm, which may present several conigurations and degrees, as well as several means of coping and dealing with the constraints. The aim of this paper is to compare the trajectories of man and women military personnel coming from the same promotion of oicers formed at the Portuguese Military Academy. Specially, we will be seeking to map their expectations regarding couplehood and parenthood besides the adopted strategies to cope and conciliate the family and the professional projects. In methodological terms, the main data will be supported on depth interviews in the form of life stories applied to the irst promotions of oicers that included women.